儒家倫理對構建醫師專業精神的若干啟示: From Confucian Ethics to Medical Professionalism - LI, Enchang; XU, Yumei; TENG, Yue (International Journal of Chinese & Comparative Philosophy of Medicine, 2008)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 《新世紀的醫師專業精神—醫師宣言》所規定的醫師專業精神的三條原則中，將患者利益放在首位原則和患者自主原則，由於諸多原因而存在著悖論。中國儒家的仁術、德教為先、修身為本、慎獨、推己及人、高度人倫的思想對解決以上悖論有啟發意義：遵循道德形成和醫學技術提高的規律，通過各種學習、強化方法，使醫者真正確立患者利益第一的專業精神和具有精湛的專業技能。從而使醫者成為患者利益的真正代表，能在各種情況下有效保護患者的利益。 As a dominant cultural tradition in China, Confucianism has greatly inf luenced the Chinese medical ethics. From the view point of Confucian ethics, medicine is the“ art of benevolence” (renshu ). For a Confucian, Confucianism and medicine share the same principle. The concept of patients-first is deeply rooted in the Confucian ethical system in which the“ virtue of a doctor” (yide ) is a primary concern in medical professionalism. This paper f irst discusses the major three principles of professionalism presented by“ The Declaration of Medical Professionalism in the New Century,” and attempts to deal with the limitations of the Declaration by introducing Confucianism with respect to healthcare professionals and a doctor-patient relationship. The paper explains that the Confucian principle of care for others determines that Confucians take human relationship very seriously in their dealing with the health issue, since they understand that a person’s health is deeply affected by, and in turnaffects, other people. Therefore, the rule of individual autonomy as well as individual right emphasized in the West should not be taken as the only legitimate one in dealing with medical issues. More importantly, that the Confucian physician considers medical practice as benevolent action and thus it is more than medical professionalism. DOWNLOAD HISTORY | This article has been downloaded 89 times in Digital Commons before migrating into this platform.